Acute Pericarditis Revealing Eosinophilic Granulomatosis with Polyangiitis Maria - Aversano, Maria Gloria; Lasagni, Giovanni; Colombo, Fabrizio; Arguello, Yuri Alessandro; Balossi, Luca Giuseppe (Archives of Clinical and Medical Case Reports, 2022)
Eosinophilic Granulomatosis with Polyangiitis (EGPA), commonly known in the past as Churg-Strauss syndrome, is a necrotizing systemic vasculitis accompanied by remarkable eosinophilia. Heart involvement occurs in approximately 15-60% of EGPA patients, especially those who are ANCA negative. Any cardiac structure can be involved. Heart involvement carries a poor prognosis and causes 50% of the deaths of these patients. It is often insidious and underestimated. Early diagnosis of cardiac involvement and subsequent therapy may prevent progression of cardiac disease. To our knowledge, so far there are only few cases reported in the literature describing pericarditis as a presenting feature of EGPA. Here we report a case of a 54- year- old male with history of repeated sinusitis and mild asthma admitted to our department for worsening dyspnea and chest pain with consequent diagnosis of acute pericarditis due to unknown EGPA. This case suggests that acute pericarditis can be the initial clinical feature of onset EGPA, even in patients with mild asthma history. Early diagnosis of cardiac involvement prevents progression of cardiac disease.